STEEL AND GFRP BEAMS/HEAVY-DUTY VEHICLE LEAF SPRINGS UNDER CYCLIC LOADING. - Fragoudakis, Roselita. (2017)
Abstract: Technological advances in many areas of the industry require of lighter and stronger materials. Especially in the automotive industry, composites have replaced many metallic components. The scope of this analysis is to determine how appropriate composite materials are for cyclic loading applications such as in the case of leaf springs. AISI 4130, AISI 6150, E glass fiber/epoxy and S2 glass fiber/epoxy were examined to determine their fatigue life and failure behavior. Experimental results, theoretical calculations and finite element analysis were performed in order to examine the important parameters that affect the fatigue life of these materials, and determine the material that will have longer life. Induction of a compressive residual stress field in a steel component, as a result of surface and heat treatment of the material, enhances the fatigue life of the material and its performance. Different ply stacking sequences of a laminate result in structures of different strength and fatigue life. Among the materials examined AISI 6150 and S2 glass fiber/epoxy have longer lives, and the steel showed longer lives than the composite at higher applied stresses. Hybrid structures were constructed from AISI 6150 and S2 glass fiber/epoxy, and examined through experimental testing and theoretical calculations, in order to determine their applicability as leaf spring structures. Comparison of the steel, composite and hybrid structures, together with an economic analysis of the manufacturing process for steel and composite leaf springs, showed that composites provide the lightest, stronger and more economical option for leaf spring material.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Mechanical Engineering.; Advisors: Anil Saigal, and Douglas Matson.; Committee: Anil Saigal, Douglas Matson, Michael Zimmerman, Georgios Savaidis, and Gary Leisk.; Keyword: Mechanical engineering.